The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14159586
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Literature Review on the Impacts of COVID-19 Pandemic on Public Road Transportation System: Challenges and Solutions

Abstract: The COVID-19 pandemic is a significant public health problem and the leading cause of reduction in the demand and supply of public transit in the last three years. It has caused an unprecedented reduction in the demand for public road transportation, and it has changed passengers’ perceptions from positive to negative when it comes to using public transportation amenities. There is an increasing concern that the public road transportation systems are witnessing a new horizon, especially now that developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…PL RP = t ns t r (P( t 0 ) − P(t)dt (5) Combined with the previous stage, the total performance loss of the system in the whole process is:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PL RP = t ns t r (P( t 0 ) − P(t)dt (5) Combined with the previous stage, the total performance loss of the system in the whole process is:…”
Section: Methodsmentioning
confidence: 99%
“…It has the characteristics of time concentration and space aggregation. The COVID-19 pandemic has boosted many studies to understand the interplay between road transport and pandemics [5][6][7]. Most findings show that the pandemic and road closure have harmed road transport [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A new train of thought in this regard emerged in 2019, when the COVID-19 outbreak caused a huge change in the behaviour and mobility of citizens across the globe [3,32]. This change mainly stemmed from the strict measures taken by governments to ensure people remained isolated and kept social distance.…”
Section: The Impact Of the Pandemic On Urban Transport Behaviour And ...mentioning
confidence: 99%
“…Several studies have reported a causal relationship between the lockdown measures imposed against COVID-19 and the decline in road traffic volume [6]. For example, Aloi et al confirmed the negative impact of lockdown and quarantine measures on road traffic volume based on recorded data from traffic control cameras and environmental sensors [7].…”
Section: Introductionmentioning
confidence: 99%